Membangun Motivasi Pelajar Untuk Melanjutkan Pendidikan Ke Jenjang Perguruan Tinggi - Sri Gustini; Dwi Umardani; Emelda; Avissa Calista (Pusat Riset dan Inovasi Nasional, 2023)
Realizing the quality and competency of people who can assist in the success of development is one of higher education's key roles. Graduates of high school, vocational school, or madrasah aliyah programs might choose to enroll in classes, work, pursue further education, or remain unemployed. They lack knowledge about scholarship information, tuition funding plans, or higher education. The implementation of this community service program aims to raise student motivation about the value of higher education for the growth of self-potential, careers, and standards of living in all facets of society. It also aims to increase knowledge, insight, understanding, and awareness about the importance of continuing education. The delivery of the subject takes the form of lectures and discuss, as well as practice sessions and individual work.